The optimal algorithm of equipment operation determined by the dynamic programming method - Добровольская, Татьяна Сергеевна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper presents an algorithm of managing the units of equipment for burning fuel of different calorific capacities in steam boilers DKVR No 20/13. Burning such kinds of fuel enables an enterprise both to reduce fuel consumption and to decrease burning expenses 13 to 19 times. The three algorithms considered in the research were: an equel distribution of the load between three boilers, between two boilers while the third one remains in reserve, and the boilers operation at the maximum load. The optimal algorithm was based on the criterion that accounted for such factors as equipment reliability and the efficiency of its use. The reliability indicator was based on such parameters as the entire time of the equipment performance, different load rates of the equipment, and the performance time beyond the rated operation. The optimal criterion was calculated by the method of dynamic programming. The criterion determined the optimal algorithm for the equipment performance with each kind of fuel. The research has shown that the suggested method for determining the optimal load management algorithm facilitates an efficient steam boilers operation. Consequently, the use of uncertified fuel allows to decrease the use of certified (purchased) fuel and to reduce the expenditure.